Inhibition of Corynebacterium pseudotuberculosis biofilm by DNA synthesis and protein synthesis inhibitors - Rashid, Syaida Anati Abd; Yaacob, Mohamad Fakhri; Aazmi, Mohd Shafiq; Jesse, Faez Firdaus Abdullah; Raja Yahya, Mohd Fakharul Zaman (Universiti Malaysia Terengganu, 2022)
Corynebacterium pseudotuberculosis represents the causative factor of caseous lymphadenitis, a ruminant disease that contributes to major economic loss in most sheep farming countries. The present study was performed to determine the efficacy of DNA synthesis (nalidixic acid) and protein synthesis inhibitors (streptomycin and tetracycline) on C. pseudotuberculosis biofilm. Biofilm of C. pseudotuberculosis clinical isolate was developed in the flat-bottom microplate. Field-emission scanning electron microscope and resazurin assay were used to investigate the structure and antimicrobial susceptibility of C. pseudotuberculosis biofilm, respectively. All test inhibitors were evaluated in the range between 3.125 μg/ml and 100 μg/ml. Results demonstrated that C. pseudotuberculosis biofilm formed a three dimensional and heterogeneous structure on the surface. The highest biofilm percentage inhibition shown by nalidixic acid, streptomycin and tetracycline were 71.57%, 87.44% and 74.73%, respectively.